The Effects of Respiratory Muscle Weakness and Pulmonary Involvement on Functional Status, Fatigue and Health Related Quality of Life in Patients With Systemic Sclerosis - Bilge KESİKBURUN,; Belma Füsun KÖSEOĞLU,; Ali ŞAHİN,; Murat TURGAY,; Asuman DOĞAN,; Öznur AYHAN ÖKEN, (Archives of Rheumatology, 2015)
Objectives: The aim of this study is to investigate the effects of respiratory muscle strength and pulmonary involvement on functional status, fatigue, and health related quality of life (HRQoL) in patients with systemic sclerosis. Patients and methods: Thirty-three patients (2 males, 31 females; mean age 46.2±13.4 years; range 27 to 77 years) with systemic sclerosis and 34 healthy volunteers (3 males, 31 females; mean age 40.9±12.8 years; range18 to 65 years) were included in the study. Pulmonary involvement and respiratory muscle strength were evaluated by measuring forced vital capacity, vital capacity, maximum voluntary ventilation, high resolution computed tomography, pulmonary artery systolic pressure, and visual analog scale for dyspnea. Functional status, HRQoL and fatigue were measured with Health Assessment Questionnaire Disability Index, Medical Outcomes Study Short Form-36 (SF-36), and Fatigue Severity Scale, respectively. Results: Compared to healthy controls, our patients had lower functional status and HRQoL, and a higher fatigue level. Respiratory muscle strength had significant contribution on functional status and SF-36 physical component summary scores. Pulmonary arterial hypertension had significant predictive value for SF-36 physical component summary. Interstitial lung disease affected the functional status only. Dyspnea had significant predictive value for fatigue and mental component summary of SF-36. Conclusion: Since a significant association is present between pulmonary involvement, respiratory muscle strength, functional status, HRQoL, and fatigue in patients with systemic sclerosis, these parameters should also be evaluated in the early period of the disease. Once respiratory muscle weakness and pulmonary involvement are detected in this population with limited treatment options, a comprehensive pulmonary rehabilitation program including respiratory muscle exercises should be designed to improve functional status, HRQoL, and fatigue.